Trust and Trustworthy Computing 8th International Conference, TRUST 2015, Heraklion, Greece, August 24-26, 2015, Proceedings - Conti, Mauro; Schunter, Matthias; Askoxylakis, Ioannis; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 8th International Conference on Trust and Trustworthy Computing, TRUST 2015, held in Heraklion, Crete, Greece, in August 2015. The 15 full papers and 3 short papers presented in this volume were carefully reviewed and selected from 42 submissions. They were organized in topical sections named: hardware-enhanced trusted execution; trust and users; trusted systems and services; trust and privacy; and building blocks for trust. There are 7 two-page abstracts of poster papers included in the back matter of the volume.
Keywords: Computer science; Computer security; Data encryption (Computer science).; Computers; Computers and civilization; Management information systems; Computer Science; Systems and Data Security; Management of Computing and Information Systems; Data Encryption; Computers and Society; Information Systems and Communication Service; Electronic books